Improving the development planning in Iran - Mehrdad Kashef; Mina Abootalebi (پژوهش‌های برنامه و توسعه)
Evaluation of Iran's development plans in different periods shows that majority of them have not achieved the desired results, and in some cases, the performance gap with the plan goals has been considerable. The evaluation of development plans shows that the lack of connection between the strategic and executive plans, and the lack of an appropriate evaluation system of the plan have been significant challenges for the realization of development plans. For this reason, suggestions have been made to improve plans in the country. These improvements include using key cores, rolling planning, or eliminating medium-term plans and focusing on adapting one-year plans with long-term plans.In this regard, this study seeks to achieve a framework of development planning that addresses the existing challenges of the country's planning system by combining the proposed improvements for planning. In the proposed framework, first, the country's development strategy and related macro goals are determined in such a way as to include the economic, social, and environmental dimensions of development and the commonalities between these three development dimensions. Then, by combining macro goals with spatial planning policies at national, regional, and provincial levels, challenges and opportunities of the country's territories are identified, so according to different spatial levels, the development drivers can be specified. In this way, sectorial and regional policies will be determined based on development drivers. In this context, combining spatial policies with macro development goals enhances the incentive and executive system for the implementation of the plan and provides the important task of the planning system, which is monitoring and evaluating the plan periodically.